MODERN METHODS OF PROSTHETIC REPAIR OF VENTRAL HERNIAS (LITERATURE REVIEW) (World Bulletin of Public Health, 2024)
According to the literature review, abdominal hernia repair is one of the most frequently performed operations worldwide. Almost all hernia plastic surgery currently performed uses some form of prosthetic materials, in particular, mesh. A huge number of meshes are implanted every year, therefore, many hernia repair products are currently on the market. This has also caused increased interest among surgeons in the relevant characteristics of the mesh, such as material, structure, price, susceptibility to infections and the body's response to the mesh
Keywords: Ventral hernias; prosthetic plastic surgery; general surgery